Value Chain Analysis Indonesian Animal Husbandry Industry - Kotim Subandi; Hermawan Hermawan; Adriana Sari Aryani (Journal of Applied Sciences and Advanced Technology, 2019)
At least until 2017, a very low production capacity coupled with livestock methods that are still traditional causes almost all major livestock commodities in Indonesia to close their deficits through imports. Meat, milk, eggs, and even the skin, all of them still cannot be fulfilled entirely from the country.As much as 83% of raw material for the dairy industry is imported. Leather processing industry, importing raw materials for cow leather by 3 million pieces and 13.5 million pieces (sheep and goat skin). Specifically for beef, it was noted that 2016 was the highest volume of beef imports reaching 132.74 thousand tons. As for eggs in general, the pattern of development of export volume is lower than the rate of imports per year. Data on chicken meat imports and their values during the 2012-2016 period showed quite high values compared to export volumes. Knowledge of industry value chains is needed to explore the gap in the dependence of imported raw materials.The value chain analysis carried out in the livestock base industry chain shows a map of the relationship between a number of livestock industry bases in Indonesia so as to facilitate the breakdown of dependence on raw materials. Analysis carried out on the main chain (livestock base) and joint chain (supporting base). Five farm-based industry value chains have been assembled, namely: 1) beef-cattle base industry; 2) industrial livestock-poultry meat base; 3) dairy-based livestock industry; 4) leather-based industry base; and 5) egg-based livestock industry. Core industries or prime movers namely: a) RPH on beef chains, b) industrial pasteurization in the milk chain; c) tanning industry on leather chains; d) food freezing industry on chicken meat chains; and e) egg packing house on the egg chain. The existence of the core industry greatly determines the position of the raw materials of the downstream industry.